Trade Induced Skill Upgrading: Lessons from the Danish and Portuguese Experiences - Grace Gu; Samreen Malik; Dario Pozzoli; Vera Rocha (Institute for the Study of Labor (IZA), 2016)
We study how the skill distribution for an economy responds to changes in the skill premium induced by trade integration. Using administrative data for Denmark (1993- 2012) and Portugal (1993-2011), we conduct a two-step analysis. In the first step we predict the skill premium changes which are triggered by exogenous trade shocks. In the second step we estimate the impact of such changes on the skill distribution. The main results for Denmark show that both the average and the standard deviation of skills increase as a result of trade integration. For Portugal we find instead that the impact of trade mediated by skill premium changes is negligible and not statistically significant. We provide a theoretical intuition to rationalize both sets of results.
Keywords: F16; J24; 330; labor market frictions; trade integration; skill upgrading; skill premium